Pedagogical Strategies in Building Students' Dance Competence: A Case Study at SMAN 1 Rengel - Rukmana, Rori Reza Dewi; Zandra, Rully Aprilia (Gondang: Jurnal Seni dan Budaya, 2025)
This research aims to identify the strategies used in learning dance at SMAN 1 Rengel and reveal the learning difficulties that arise in implementing these strategies. Using a descriptive qualitative approach, this research collects data through observation, interviews and documentation. The data analysis techniques used include data collection, data reduction, data presentation, and drawing conclusions. The results of this research show that the strategy used was a combination of the Project-Based Learning (PjBL) method and peer tutoring which was proven to be effective in developing the dancing skills of class XI E students at SMAN 1 Rengel. PjBL encourages active student engagement through real projects, while peer tutoring increases motivation, collaboration, and mastery of dance moves. However, there are learning difficulties that arise in implementing this strategy, such as differences in skill levels with recommendations to overcome them, it is recommended to implement training that focuses on small groups, lack of interest in the art of dance with recommendations to overcome them, it is recommended to implement training that focuses on small groups, limitations time with recommendations to overcome it, it is recommended that flexible training scheduling be provided, inadequate facilities with recommendations for overcoming it are recommended to maximize the use of existing facilities, as well as difficulties in understanding dance movements through YouTube video media with recommendations for overcoming it is recommended to implement training that focuses on groups small. The implication obtained is that it makes a real contribution in improving the quality of dance learning at SMAN 1 Rengel.